2017
DOI: 10.1056/nejmoa1611930
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against GPIHBP1 as a Cause of Hypertriglyceridemia

Abstract: BACKGROUND A protein that is expressed on capillary endothelial cells, called GPIHBP1 (glycosylphosphatidylinositol-anchored high-density lipoprotein binding protein 1), binds lipoprotein lipase and shuttles it to its site of action in the capillary lumen. A deficiency in GPIHBP1 prevents lipoprotein lipase from reaching the capillary lumen. Patients with GPIHBP1 deficiency have low plasma levels of lipoprotein lipase, impaired intravascular hydrolysis of triglycerides, and severe hypertriglyceridemia (chylomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(175 citation statements)
references
References 31 publications
1
174
0
Order By: Relevance
“…As negative controls, we included samples from a subject who was homozygous for a deletion of the entire GPIHBP1 gene 3 and two subjects who had a GPIHBP1-C89X nonsense mutation. 1 As expected, the GPIHBP1 serum levels in the “negative control samples” ( i.e. , samples from patients with GPIHBP1 mutations) were very low.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…As negative controls, we included samples from a subject who was homozygous for a deletion of the entire GPIHBP1 gene 3 and two subjects who had a GPIHBP1-C89X nonsense mutation. 1 As expected, the GPIHBP1 serum levels in the “negative control samples” ( i.e. , samples from patients with GPIHBP1 mutations) were very low.…”
Section: Resultssupporting
confidence: 61%
“…1 We had no difficulty in detecting GPIHBP1 in the plasma of a hypertriglyceridemic patient who had a genetic deficiency in LPL , whereas GPIHBP1 levels were extremely low in hypertriglyceridemic patients who had loss-of-function mutations in GPIHBP1 (missense, nonsense, or deletion). 1 In patients with GPIHBP1 deficiency, the plasma LPL levels were also low, reflecting markedly reduced delivery of LPL to the capillary lumen. 1 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We have recently reported that the autoantibody against GPIHBP1 completely blocked LPL activity and induced severe hypertriglyceridemia without forming CM and VLDL remnants even after food intake [45]. Figure 4: LPL is secreted from adipocytes and move to interstitial space.…”
Section: Formation Of Remnant Lipoproteins By Lpl At Endotheliummentioning
confidence: 99%